Letter from R.R. Bennett to Jane Tolmach January 31, 1973 - R.R. Bennett:::::: (1973)
A letter sent to Jane Tolmach discussing a cooperative agreement made between Oxnard, Camarillo, and Ventura County in regards to the former Oxnard Air Force Base.